Antimicrobial resistance profile of Methicillin-resistant Staphylococcus aureus colonizing the anterior nares of health-care workers and outpatients attending the remotely located tertiary care hospital of North India - Seema Singh (Journal of Laboratory Physicians, 2017)
INTRODUCTION: Resistance to antimicrobial agents is a major concern worldwide and is exemplified by the global spread of the Methicillin resistant Staphylococcus aureus (MRSA). Health care workers (HCWs) and asymptomatically colonized patients are important sources of nosocomial MRSA infections. AIMS AND OBJECTIVES: To determine the prevalence of MRSA colonisation, two hundred HCWs and 200 consecutive outpatients attending our tertiary care hospital were studied. MATERIALS AND METHODS: Two sterile pre-moistened cotton tipped swabs were used to collect specimens from their anterior nares. These were inoculated immediately on Blood agar with oxacillin, Mannitol salt agar with oxacillin and CHROM agar. Resistance to cefoxitin was confirmed by PCR by demonstration of mecA gene. Antibiotic susceptibility was determined by Kirby Bauer’s disc diffusion method and MIC of vancomycin by using broth dilution and Vitek-2 Compact system. RESULTS: The nasal carriage of MRSA among HCWs was found to be 7.5% and in outpatients 3%. All strains of MRSA from HCWs and outpatients grew on three selective media and mecA gene amplified in all of them. All the isolated strains of MRSA showed high degree of resistance to co-trimoxazole (93.3%), ciprofloxacin (80%) and erythromycin (66.66%). However, there was 100% susceptiability to vancomycin, teicoplanin, linezolid and Rifampicin. CONCLUSION: Although a direct casual relationship could not be established, it could be assumed that the transmission from colonised health care worker is responsible atleast in part for MRSA infection among patients. Therefore emphasis should be laid on strict implementation of standard infection control practices which would help in minimizing the carriage and transmission of MRSA in the hospital.